Efficacy of a joint supplement containing eggshell membrane among other ingredients to improve the mobility of dogs with osteoarthritis: a multicenter double-blind randomized placebo-controlled study - Ragetly, Guillaume R.; Martins, Ângela; Ober, Ciprian A.; Boiocchi, Silvia; Nicolas, Céline S. (Frontiers in Veterinary Science, 2025)
The management of osteoarthritis (OA) in dogs is typically multimodal, including weight management, activity adjustment, joint supplements, and medical treatments when needed. This study evaluated the efficacy of a joint supplement containing eggshell membrane, krill meal with omega-3 fatty acids, Haematococcus pluvialis as a source of astaxanthin, hyaluronic acid and a Boswellia Serrata extract, in dogs with OA, in a multicenter, randomized, placebo-controlled trial. Fifty-two dogs with confirmed OA were given the test supplement or a placebo, for 90 days. Owners regularly completed two validated questionnaires for osteoarthritis (CBPI and LOAD) and rated their dog’s discomfort every 15 to 30 days. Monthly evaluations by investigators included assessments of the dog’s posture, gait, joint pain upon palpation and range of motion (from 1-normal to 4-severe or severely impacted) to determine a clinical score. Statistical analyses included both within-group and between-group comparisons. Of the 52 dogs enrolled, 46 completed the study, with 22 receiving the supplement and 24 receiving the placebo. All main parameters significantly improved over time in the supplement group (CBPI pain severity, CBPI pain interference, LOAD, discomfort, clinical score). In the placebo group, only the CBPI pain interference and LOAD improved. However, there was a statistically significant difference between groups for the CBPI pain interference (p = 0.009). Therefore, this study demonstrates that the test supplement can improve the mobility and quality of life of osteoarthritic dogs.